Ensuring Compliance with the Principle of Tafriq al-halal ‘an al-haram in Sharia Syndicated Financing: A Sharia Economic Law Perspective - Desi Siti Habibah Arifin; Siti Afifah; Muhammad Asep Saiful Millah (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2024)
The research investigates the implementation of the principle of tafriq al-halal ‘an al-haram in Islamic syndicated financing within the framework of Islamic economic law. Employing a normative juridical method and a conceptual approach, the research examines the foundational legal and ethical considerations that guide contract selection, risk-sharing, and compliance in multi-institutional syndication schemes. The research identifies key challenges, including divergent interpretations of Sharia among syndicate members, difficulties in structuring legally valid yet Sharia-compliant documentation, and the absence of interest-based penalties in cases of default. To address these issues, the research proposes several practical solutions, such as the use of standardized Sharia governance frameworks, the role of lead arrangers in harmonizing compliance, and the integration of transparent risk-sharing mechanisms based on musyarakah or mudharabah contracts. The consistent implementation of the tafriq al-halal ‘an al-haram principle is found to be instrumental not only in ensuring Sharia compliance in complex financial structures but also in enhancing public trust and fostering the sustainable development of the Islamic financial industry.